2, 3, 5, 4′-Tetrahydroxystilbene-2-O-β-D-glucoside prevention of lipopolysaccharide-induced depressive-like behaviors in mice involves neuroinflammation and oxido-nitrosative stress inhibition. Issue 5 (August 2017) - Chen, Zhuo; Huang, Chao; He, Haiyan; Ding, Wenbin
Abstract : Although numerous hypotheses have been raised in recent years, the exact mechanisms that promote the development of major depression are largely unknown. Recently, strategies targeting the process of neuroinflammation and oxidative stress in depression have been attracting greater attention. 2, 3, 5, 4′-Tetrahydroxystilbene-2-O-β-D-glucoside (TSG), a compound purified from a traditional Chinese herbal medicine polygonummultiflorum, has been widely reported to inhibit neuroinflammation and oxidative stress. In this context, we investigated whether TSG affects lipopolysaccharide (LPS)-induced depressive-like behaviors in a manner associated with neuroinflammation and oxido-nitrosative stress. Results showed that administration of ICR mice with 0.83 mg/kg of LPS-induced typical depressive-like behaviors in the experiments of the tail-suspension test, the forced-swimming test, and sucrose preference, and these behaviors were prevented by TSG treatment (30 and 60 mg/kg). Further analysis showed that TSG pretreatment at the doses of 30 and 60 mg/kg not only inhibited the production of proinflammatory cytokines induced by LPS, such as interleukin-1β, interleukin-6, and tumor necrosis factor-α, but also prevented the LPS-induced enhancement of oxido-nitrosative stress in mouse hippocampus and prefrontal cortex. The LPS-induced decreases in brain-derived neurotrophic factor levels in the hippocampus and prefrontal cortex were also prevented by TSG treatment. Generally, our data provide evidence to show that TSG could be used to cope with depressive-like symptoms by inhibition of neuroinflammation and oxido-nitrosative stress.